The Impact of EWOM (Electronic Word of Mouth) on Purchase Intention through Brand Image (A Case Study on GoPro Camera) in Malang City - Fachrozie, Septiawan Vergian (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research used some concepts to analysis data. That concepts are marketing, Word of Mouth Communication, Electronic Word of Mouth (eWOM) Communication, brand image, and purchase intentions. The method of this research is descriptive method with quantitative approach. In this research were used as the population is people who live in Malang City that use GoPro camera or GoPro user that use GoPro or Rent GoPro. Number of population user GoPro camera that comes from an unknown people who have a GoPro and people who rent camera GoPro, so this research used accidental sampling to sampling technique. Researchers determine the sample to make searching on social media with the keyword camera GoPro. Then the data analysis techniques used in this research is descriptive data analysis and regression analysis using quantitative research approaches, This research stated that the calculation results of path coefficient of Electronic Word of Mouth (EWOM) have a significant Influence to Purchase Intention as big as 0,865. Then the calculation results of path coefficient of Electronic Word of Mouth (EWOM) have a significant Influence to Brand Image as big as 1,056. The last the calculation results of path coefficient of Electronic Word of Mouth (EWOM) have a significance Influence to Purchase Intention through Brand Image as big as 0,916 with significant value as big as 0,000 (sig probability < 0,05).Keywords: Electronic Word of Mouth (eWOM) Communication, Brand Image, Purchase Intention